Descripción de la cadena de comercialización de cacao y su impacto socioeconómico de los productores en el Ecuador - Aspiazu Rodríguez, Keily Selene (2023)
Cocoa comes from South America in Ecuador exactly in the Amazon basin which produces a fruit that is used as an ingredient for different foods and specifically for chocolate. Cocoa and its derivatives have a wide demand internationally, being the raw material for various productions in the chocolate industry. Within marketing, its physical characteristics play a fundamental role in this entire process. The objective of this work is to describe the cocoa marketing chain in our country and to know the socioeconomic impact for producers. The results obtained demonstrate that the actors involved in marketing are farmers, collectors, intermediaries, exporters, distributors and finally consumers who are the ones who already acquire the final product for consumption. The cultivation of cocoa has a significant socioeconomic impact for the country; this fruit is one of the most exported products and has helped both economic growth and the well-being of agricultural populations. The marketing of cocoa in Ecuador is influenced by intermediaries who are the main ones in doing business with farmers, these being the most benefited in the entire marketing process. To prepare the document, information was collected from current documents, virtual libraries, scientific articles and websites, which helped in the contribution of opinions and ideas from authors that allowed studying the development of this research.